An in situ photocrosslinkable platelet rich plasma – Complexed hydrogel glue with growth factor controlled release ability to promote cartilage defect repair. (15th October 2017) - Liu, Xiaolin; Yang, Yunlong; Niu, Xin; Lin, Qiuning; Zhao, Bizeng; Wang, Yang; Zhu, Linyong
Graphical abstract: Abstract: The repair of articular cartilage injury is a great clinical challenge. Platelet-rich plasma (PRP) has attracted much attention for the repair of articular cartilage injury, because it contains various growth factors that are beneficial for wound repair. However, current administration methods of PRP have many shortcomings, such as unstable biological fixation and burst release of growth factors, all of which complicate its application in the repair of articular cartilage and compromise its therapeutic efficacy. In this study, based on our previously reported photoinduced imine crosslinking (PIC) reaction, we developed an in situ photocrosslinkable PRP hydrogel glue (HNPRP) through adding a photoresponsive hyaluronic acid (HA-NB) which could generate aldehyde groups upon light irradiation and subsequently react with amino groups, into autologous PRP. Our study showed that HNPRP hydrogel glue was cytocompatible and could be conveniently and rapidly prepared in situ, forming a robust hydrogel scaffold. In addition, our results demonstrated that HNPRP hydrogel not only achieved controlled release of growth factors, but also showed strong tissue adhesive ability. Therefore, HNPRP hydrogel was quite suitable for cartilage defect regeneration. Our further in vitro experiment showed that HNPRP hydrogel could promote the proliferation and migration of chondrocytes and bone marrow stem cells (BMSCs). In vivo testing using a rabbit full-thickness cartilage defect model demonstrated that HNPRP hydrogel could achieve integrative hyaline cartilage regeneration and its therapeutic efficacy was better than thrombin activated PRP gel. Statement of Significance: In this study, we have developed a photocrosslinkable platelet rich plasma (PRP) – complexed hydrogel glue (HNPRP) for cartilage regeneration. The in situ formed HNPRP hydrogel glue showed not only the controlled release ability of growth factors, but also strong tissue adhesiveness, which could resolve the current problems in clinical application of PRP. Furthermore, HNPRP hydrogel glue could promote integrative hyaline cartilage regeneration, and its reparative efficacy for cartilage defect was better than thrombin activated PRP gel. This study provided not only an effective repair material for cartilage regeneration, but also developed an advanced method for PRP application.